Participation in the workplace: gender perspectives from Bangladesh - Andaleeb, Syed Saad; Wolford, Gretchen Vanneman (© 2004 Emerald Group Publishing Limited, 2016)
This article was published in the Women in Management Review [© 2004 Emerald Group Publishing Limited] and the definite version is available at : http://dx.doi.org/10.1108/09649420410518430 The Journal's website is at: http://www.emeraldinsight.com/doi/full/10.1108/09649420410518430